Characteristics of speargrass (Imperata cylindrica) dominated fields in West Africa: crops, soil properties, farmer perceptions and management strategies - Chikoye, David; Manyong, Victor M.; Ekeleme, F. (Elsevier, 2000)
Speargrass is a dominant, competitive and difficult weed to control in tropical Asia, Latin America, and some parts of West Africa. In West Africa, no information is available on the cropping systems and soils most affected by speargrass infestation; Farmers’ perceptions of speargrass and common management strategies employed by farmers are unknown. Surveys were conducted in 1996 and 1997 in the coastal/derived savanna (Benin and Nigeria) and southern Guinea savanna (Côte d'Ivoire) to characterize farming systems, soils, and farmers’ management strategies in fields dominated by speargrass. Twenty-one crops were found in speargrass dominated fields. Speargrass was ranked as the most serious weed in both agroecological zones. Besides speargrass, Commelina benghalensis L., Digitaria nuda Shumach, Cyperus rotundus L., Tridax procumbens L., Rottboellia cochinchinensis (Lour.) Clayton, Digitaria horizontalis Willd, Striga spp., and Euphorbia heterophylla were also considered as important weeds in major cropping systems. Speargrass was undesirable because it reduces crop yield and quality, limits farm size, causes injury to the skin, increases labour requirement and increases the presence of pathogens and insects of economic crops. Nevertheless, some farmers indicated that speargrass was an important source of cheap roofing material, animal fodder and medicines. Most farmers used labour intensive control strategies to combat speargrass due to, among other reasons, lack of capital. Speargrass occurred in soils with a wide range of chemical properties and particle size distribution.